Comparison of vertically sided model structures with circular and rectangular cross section subjected to ice-induced vibrations in the frequency lock-in regime - Owen, Cody Carlton (NTNU, 2017)
Very recently, offshore wind energy has begun expanding into subarctic regions with seasonally ice-infested waters like the Baltic Sea. For offshore wind turbines with conventional support structures including monopiles and jackets that are typically flexible and vertically sided, the phenomenon known as ice-induced vibrations can develop. In response to the growing interest in offshore wind in the Baltic Sea and in further validating a state-of-the-art numerical model for ice-structure interaction, the Ice-induced Vibrations of Offshore Structures (IVOS) project has been coordinated with the Hamburg Ship Model Basin (HSVA) and many academic and industry partners including TU Delft and NTNU in order to enhance understanding of the topic via a comprehensive laboratory testing campaign. In this thesis, specific data are selected from the extensive IVOS Phase 2 tests such that a comparative analysis is performed between two different model-scale structures, one with circular cross-section and another with rectangular cross-section, that were subjected to ice-induced vibrations in the frequency lock-in regime. Preceding the comparative analysis, the data from the IVOS Phase 2 tests are organized into a database and post-processing tools are developed to facilitate further research by supplying analysis-ready data sets. Included in the post-processing tools is an attempt to determine ice-induced global loads from uncalibrated tactile sensor data, which offers insight into the relationship between the relative pressure distributions along the ice-structure interface and the ice-induced global forces on the model structure. The comparative analysis garnered qualitative information about the frequency lock-in regime and buckling failure of ice. It is observed that frequency lock-in vibrations usually persisted regardless of buckling events. For the frequency lock-in regime, the ice-induced global loads on the circular cross-section structure are generally lower than those for the rectangular cross-section structure. It ...